Effect of deletion of gene cluster involved in synthesis of Enterobacterial common antigen on virulence and immunogenicity of live attenuated Salmonella vaccine when delivering heterologous Streptococcus pneumoniae antigen PspA - Qing Liu; Xuegang Shen; Xiaoping Bian; Qingke Kong (BMC Microbiology, 2020)
Abstract Background Enterobacterial common antigen (ECA) is a family-specific surface antigen shared by all members of the Enterobacteriaceae family. Previous studies showed that the loss of ECA results in Salmonella attenuation, indicating its usefulness as a vaccine candidate for Salmonella infection, but no studies have shown whether the mutation resulting from the deletion of the ECA operon in conjunction with other mutations could be used as an antigen vehicle for heterologous protein antigen delivery. Results In this study, we introduced a nonpolar, defined ECA operon deletion into wild-type S. Typhimurium χ3761 and an attenuated vaccine strain χ9241, obtaining two isogenic ECA operon mutants, namely, χ12357 and χ12358, respectively. A number of in vitro and in vivo properties of the mutants were analyzed. We found that the loss of ECA did not affect the growth, lipopolysaccharide (LPS) production and motility of S. Typhimurium wild type strain χ3761 and its attenuated vaccine strain χ9241 but significantly affected the virulence when administered orally to BALB/c mice. Furthermore, the effects of the ECA mutation on the immunogenicity of a recombinant S. Typhimurium vaccine strain χ9241 when delivering the pneumococcal antigen PspA were determined. The result showed that the total anti-PspA IgG level of χ12358 (pYA4088) was slightly lower than that of χ9241 (pYA4088), but the protection rate was not compromised. Conclusions ECA affects virulence and benefits the Th2 immunity of Salmonella Typhimurium, therefore, it is feasible to use a reversible ECA mutant mode to design future Salmonella vaccine strains for heterologous protective antigens.